RESIDIVISME ANAK PELAKU TINDAK PIDANA: ANALISIS KRIMINOLOGIS DAN FAKTOR PENYEBAB DI LPKA TENGGARONG - Kristy Siuling Lai; Rini Apriyani; Ine Ventyrina (Universitas Labuhanbatu, 2026)
Juvenile recidivism represents a significant criminological issue, reflecting the limited effectiveness of rehabilitation within the juvenile justice system. The return of child offenders to correctional institutions indicates the presence of underlying factors that contribute to reoffending, as well as gaps in the current rehabilitation approach. This study aims to analyze the criminological factors influencing juvenile recidivism and to evaluate the rehabilitation programs implemented at the Class II Juvenile Correctional Institution (LPKA) in Tenggarong. The research employs a socio-legal approach, combining empirical data obtained through interviews with secondary data derived from statutory regulations, academic literature, and relevant studies. The findings reveal that juvenile recidivism is influenced by multiple factors, including social environment, prisonization effects, social media exposure, economic conditions, low educational attainment, and inadequate supervision. Although the institution has implemented various rehabilitation programs—such as personality development, religious guidance, legal awareness, intellectual training, and vocational skills—these efforts have not been fully effective in preventing reoffending. This study highlights the need for a more integrative and sustainable rehabilitation model that involves family support, community participation, and post-release supervision to reduce juvenile recidivism. From a criminological perspective, this research contributes to understanding the interplay between institutional rehabilitation and social factors in shaping recidivist behavior among juveniles. Keywords: Juvenile Recidivism, Criminology, Juvenile Correctional Institution, Rehabilitation